2021
DOI: 10.1101/2021.03.04.433896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Translational evidence for RRM2 as a prognostic biomarker and therapeutic target in Ewing sarcoma

Abstract: Purpose: Ewing sarcoma (EwS) is a highly aggressive bone- or soft tissue-associated malignancy mostly affecting children, adolescents, and young adults. Although multimodal therapies have strongly improved patients′ overall survival over the past decades, the development of prognostic biomarkers for risk-based patient stratification and more effective therapies with less adverse effects is stagnating. Thus, new personalized medicine approaches are urgently required. Experimental design: Gene expression data of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…The effects of nucleotide inhibition by RNR inhibitors or RRM2 knockdown on CHK1 levels have been reported by several teams ( 61 , 62 ). Particularly instructive is the recent work of Ohmura et al in Ewing sarcoma ( 23 ), who demonstrated that, upon exposure to the gemcitabine RNR inhibitor, total CHK1 is down-regulated together with down-regulation of global protein levels. These authors also showed that, upon RRM2 knockdown, similar results are observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of nucleotide inhibition by RNR inhibitors or RRM2 knockdown on CHK1 levels have been reported by several teams ( 61 , 62 ). Particularly instructive is the recent work of Ohmura et al in Ewing sarcoma ( 23 ), who demonstrated that, upon exposure to the gemcitabine RNR inhibitor, total CHK1 is down-regulated together with down-regulation of global protein levels. These authors also showed that, upon RRM2 knockdown, similar results are observed.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for a more direct role of RRM2 in cancer formation or maintenance comes from mouse models in which increased RRM2 expression promotes lung ( 19 ), breast ( 20 ), and prostate cancer ( 21 ). Furthermore, RRM2 dependency was demonstrated in BRAF V600E -driven melanoma ( 22 ) and Ewing sarcoma ( 23 ). Of further interest, RRM2 was shown to be the target of synthetic lethal interaction with G2 Checkpoint Kinase (WEE1) inhibition in H3K36me3-deficient cancers ( 12 ).…”
Section: Introductionmentioning
confidence: 99%